7 - Hip-Hop and Bongo Flavour Music in Contemporary Tanzania:Youths’ Experiences, Agency, Aspirations and Contradictions - Suriano, Maria (Africa Development, 2021)
The beginning of Tanzanian hip-hop along with a genre known as Bongo Flavour (also Bongo Flava, or Fleva, according to the Swahili spelling), can be traced back to the early 1990s. This music, characterised by the use of Swahili lyrics (with a few English and slang words) is also re- ferred to as the ‘music of the new generation’ (muziki wa kikazi kipya). Without the intention to analyse a complex and multifaceted reality, this article aims to make a sense of this popular music as an overall phenom- enon in contemporary Tanzania. From the premise that music, perform- ance and popular culture can be used as instruments to innovate and produce change, this article argues that Bongo Flavour and hip-hop are not only music genres, but also cultural expressions necessary for the understanding of a substantial part of contemporary Tanzanian youths. The focus here is on young male artists living in urban environments.